2017
DOI: 10.18632/oncotarget.18755
|View full text |Cite
|
Sign up to set email alerts
|

Tumor p38MAPK signaling enhances breast carcinoma vascularization and growth by promoting expression and deposition of pro-tumorigenic factors

Abstract: The breast carcinoma microenvironment strikingly influences cancer progression and response to therapy. Various cell types in the carcinoma microenvironment show significant activity of p38 mitogen-activated protein kinase (MAPK), although the role of p38MAPK in breast cancer progression is still poorly understood. The present study examined the contribution of tumor p38MAPK to breast carcinoma microenvironment and metastatic capacity. Inactivation of p38MAPK signaling in metastatic breast carcinoma cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 51 publications
4
41
0
Order By: Relevance
“…As reported earlier in other cell types, sorafenib downregulated phosphorylated levels of p38MAPK [25,34] and STAT5 [35,36] in MDA-MB-231 cells. Activation of p38MAPK has been found to transduce metastatic signaling and proliferation [11], whereas STAT5 signaling promotes tumor growth and metastasis in breast cancer cells [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported earlier in other cell types, sorafenib downregulated phosphorylated levels of p38MAPK [25,34] and STAT5 [35,36] in MDA-MB-231 cells. Activation of p38MAPK has been found to transduce metastatic signaling and proliferation [11], whereas STAT5 signaling promotes tumor growth and metastasis in breast cancer cells [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer stem cells contribute toward the development of metastasis because of their inherent resistance to chemotherapeutic drugs. Activation of intracellular signaling pathways such as ERK1/2 and p38 MAPK have been shown to advance tumor progression [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, p38 modulates the expression of pro-angiogenic factors such as HBEGF, IL-8 and VEGFA in metastatic breast carcinoma cells. Inhibition of stress-activated p38 reduces primary tumor growth in orthotopic xenograft models and the number of lung metastatic colonies after tail-vein injection [111]. Although these findings support the prometastatic role of the p38 pathway, it has been reported that p38-knockdown human colorectal cancer cells show a greater capacity to colonize the lung in an orthotropic xenograft mouse model [112].…”
Section: P38 Mapk As a Tumor Promotermentioning
confidence: 92%
“…The inactivation of the p38/MAPK signaling pathway was provided by the expression of the kinase-inactive mutant (dn-p38) of p38/MAPK14 in metastatic breast cancer cells in the studies, and with the deterioration of the tumor p38/MAPK signal, the development of breast cancer and metastasis ability was shown to decrease in breast carcinoma xenografts [9]. The conducted kinase-inactive mutant significantly decreased the dn-p38, tumor blood vessel density, and lumen dimensions.…”
Section: P38/mapk Pathwaymentioning
confidence: 99%
“…The deterioration of p38/MAPK signal causes no decrease in the expression of MMP9 and ICAM1 that are secreted by tumor cells. p38/MAPK signal contributes to fibronectin expression by responding to cytokines and tumor-fibroblast interactions [9].…”
Section: P38/mapk Pathwaymentioning
confidence: 99%